Exploring patterns in math & beyond : (Grades K-2) - Franco, Betsy (New York : Scholastic Professional Books, 1999)
30 easy, playful & creative patterning activities that teach across the curriculum.
Keywords: Mathematics--Study and teaching; Mathematics--Activities